The role of computed tomography in diagnosing the vulnerability of carotid artery plaques (literature review) - L. E. Galyautdinova; A. A. Rakhmanova; Ya. A. Filin; I. V. Basek; D. V. Alekseeva; G. E. Trufanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Atherosclerotic lesion of the extracranial carotid arteries is one of the main causes of ischemic stroke. Computed tomography is a widely available, non-invasive method that allows us to evaluate not only the anatomical features of the brachiocephalic arteries and the degree of stenosis, but also the structure of the plaque. In recent years, there has been increasing evidence of an association of ischemic stroke not only with the degree of stenosis, but also with the presence of plaque vulnerability. Identification of signs of plaque instability using non-invasive diagnostic methods, such as CT angiography, has the potential to evaluate the risk of vascular events, reduce the need for invasive diagnosis, and facilitate timely identification of indications for surgical intervention.